Aroma Electric Therapy Equipment with Atmega8 -Based Heart Rate Monitoring - Sigit Widadi; Zulfikar Adli Manzila; Irfan Ahmad; Omar tanane (Journal of Robotics and Control (JRC), 2020)
Aromatherapy is an alternative treatment method that uses essential oil vapours from various plants inhaled for health therapy. It affects mood, reduces fatigue and anxiety, and stimulates relaxation. Relaxation is the process of relieving anxiety or stress. It is interpreted as a calm state with a normal pulse. When someone is stressful and anxious, the pulse is higher. Measuring the level of anxiety is done by measuring the heart rate. The research aimed to design an electric aromatherapy device equipped with Atmega 8-based heart rate monitoring as a therapeutic tool that can help reduce various kinds of health problems, one of which is anxiety or stress disorder. The test was carried out by comparing the values of the heart rate monitoring to a pulse oximeter. The oximeter was used as a reference to get high accuracy values. The device is expected to help reduce various kinds of health problems caused by heart problems.